STUDI PERAN SISTEM INFORMASI AKUNTANSI PENJUALAN PADA USAHA KECIL MENENGAH - Burhanuddin Bani; Siti Komariyah (JEM Jurnal Ekonomi dan Manajemen, 2020)
Sales activity is an important activity for the survival of the company, including SMEs. Factors that can affect the level of sales of a company include consumer needs, product competition, economic conditions, and product marketing, so that good administrative management is needed, one of which is recording sales quickly and effectively in order to produce informative sales reports for management. This study aims to analyze sales accounting information procedures at PT. Jagorawi Motor Bangka Belitung, using the descriptive-analytic method. The study concluded that PT. Jagorawi Motor has carried out sales accounting information procedures well and also involved several parts in sales accounting information procedures which are almost the same as the literature. It's just that this process in the literature is explained directly by function, but in companies, it is more detailed by involving its parts and functions. The recommendation from the study is that the section related to sales accounting information procedures maintain good procedures and can improve internet connections so that there are no interruptions when inputting data.